FINANCIAL PLANNING, FORECASTING AND BUDGETING IN CORPORATE GOVERNANCE INFRUSTRUCTURE - ALEKSIN, Glib (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The volatility of both the exogenous and endogenous business environment necessitates leveraging the full potential of financial management within the framework aimed at creating value for stakeholders. Corporate governance is a key element in this context, ensuring the appropriate course of business development and alignment with stakeholder interests. This paper examines the key aspects of implementing a comprehensive approach to financial management from the perspective of corporate governance. The paper emphasizes the role of financial planning, forecasting, and budgeting as tools for ensuring resource efficiency, strategic thinking, and accountability to stakeholders. From a corporate governance perspective, the mechanisms of financial planning (analysis of the exogenous and endogenous environment, financial models), financial forecasting (scenario analysis, regression analysis), and budgeting (detailing and controlling the implementation of strategic plans and forecasts) are examined to assess risks and development opportunities. These tools may be specifically applied to form a trajectory for achieving goals based on ESG criteria, which is among the key contemporary objectives of corporate governance. The advantages of automation and analytics in enhancing the transparency of financial management and accelerating decision-making within corporate governance infrastructure are highlighted. The integration of this framework into the corporate governance system serves as an effective tool for mitigating risks and enhancing managerial accountability to stakeholders. The implementation of this mechanism incorporates elements of CSRD 2022/2464/EU, which consolidates the reporting of both financial and non-financial metrics of companies. It is emphasized that the integration of this complex into corporate governance contributes to risk reduction, increased transparency, and accountability to shareholders, while ensuring the sustainable development of the company and enhancing its managerial discipline. Prospects for further research include the development of methods for integrating the complex of financial planning, forecasting, and budgeting into the corporate governance infrastructure.
Keywords: financial planning; forecasting; budgeting; corporate governance; financial management; risk; stakeholder; ESG; CSRD